Impact of flow velocity on the heterogeneous reaction of SO2 over Fe2O3. (1st February 2023) - Liu, Yangyang; Wang, Tao; Ge, Qiuyue; Shi, Zhuocheng; Li, Kejian; Gong, Kedong; Xie, Lifang; Wang, Wei; Wang, Qianlong; Han, Jin; Fu, Hongbo; Chen, Jianmin; et al.
Abstract: Flow velocity, potentially linked to dry deposition velocity and wind speed parameters, show non-marginal significance in the heterogeneous oxidation of SO2 on α-Fe2 O3 particles. Our uptake measurement results produce lab-based evidence that an increase in flow velocity can potentially strengthen SO2 uptake capability over α-Fe2 O3 by nearly one order of magnitude within the range of considered reaction conditions. Additionally, specimen analysis of surface S-containing products indicates a distinct SO2 oxidation regime, shifting from the heterogeneous reaction mediated by active sites under low flow velocity and low RH to an aqueous-like multiphase-dominated pathway under high flow velocity and high RH. An attempt was further made to link this experimental parameter to dry deposition velocity regulated by wind force in the atmosphere. This work highlights the significance of flow velocity in triggering fast sulfate production concerning dust chemistry. Graphical abstract: Image 1 Highlights: High flow velocity potentially induces fast sulfate formation in the atmosphere. SO2 uptake coefficient is increased by over 10 times at high flow velocity. This force alters both surface sulfur species and the reaction regime.